SLCO1B1 gene variations among Tanzanians, Ethiopians, and Europeans: relevance for African and worldwide precision medicine - Aklillu, Eleni; Habtewold, Abiy; Ngaimisi, Eliford; Yimer, Getnet; Mugusi, Sabina; Amogne, Wondwossen; Reuter, Tasmin; Meid, Andreas; Hoffmann, Michael Marcus; Weiß, Johanna (OMICS, 2016)
The solute carrier organic anion transporter family member 1B1 (SLCO1B1) gene encodes for a membrane-bound organic anion transporter protein involved in active cellular influx of many endogenous compounds and xenobiotics. SLCO1B1 genetic variation is associated, for example, with highly variable rifampicin exposure, thus influencing the cornerstone antituberculosis therapy, especially in sub-Saharan Africa where it is a key therapeutic modality. Yet, there is no SLCO1B1-guided pharmacogenetic dosing recommendation for rifampicin to reduce the risk of adverse events or therapy failure. Accordingly, comparative characterization of SLCO1B1, particularly within understudied African populations, is crucial and timely for global precision medicine, given the importance of antituberculosis therapy worldwide. Therefore, we report here the allele, genotype, and haplotype frequencies for common SLCO1B1 gene polymorphisms among Europeans (N = 57), Tanzanians (N = 361), and Ethiopians (N = 632). Our results show that the allele frequencies of rs4149032T, rs2306283G, rs11045819A, and rs4149056C differ significantly among Ethiopians (48.1%, 60.3%, 2.8%, 19.1%). Tanzanians (51.9%, 86.8%, 4.7%, 3.2%), and Europeans (19.8%, 34.2%, 7.9%, 22.8%) (p < 0.001). Notably, the most common haplotypes in Tanzanians (TGCT; g.38664T + c.388G + c.463C + c.521T = 61.1%) and Europeans (CGCT, all wild-type SLCO1B*1A = 59.8%) occurred at a much lower frequency in Ethiopians (TGCT = 38.8% and CGCT = 31.6%) (p < 0.0001). Additionally, the nonfunctional SLCO1B1 haplotypes CGCC (*15) and CACC (*5) are relatively common or detectable in Ethiopians (14.1%, 3.2%, respectively) and Europeans (18.1%, 2.8%) but rare in Tanzanians (1.9% and 0%, respectively) (p < 0.001). These new observations collectively underscore that precision medicine for rifampicin and other cornerstone therapeutics will require a comparative study of each and every population in the African continent as well as globally. SLCO1B1 and its extensive within- and between-population variations have to be carefully borne in mind for global precision medicine.
Gesehen am 13.08.2020